Prevalence, awareness, treatment, and control of hypertension in Nigeria in 1995 and 2020: A systematic analysis of current evidence. Issue 5 (18th February 2021) - Adeloye, Davies; Owolabi, Eyitayo O.; Ojji, Dike B.; Auta, Asa; Dewan, Mary T.; Olanrewaju, Timothy O.; Ogah, Okechukwu S.; Omoyele, Chiamaka; Ezeigwe, Nnenna; Mpazanje, Rex G.; Gadanya, Muktar A.; Agogo, Emmanuel; et al.
Abstract: Improved understanding of the current burden of hypertension, including awareness, treatment, and control, is needed to guide relevant preventative measures in Nigeria. A systematic search of studies on the epidemiology of hypertension in Nigeria, published on or after January 1990, was conducted. The authors employed random‐effects meta‐analysis on extracted crude hypertension prevalence, and awareness, treatment, and control rates. Using a meta‐regression model, overall hypertension cases in Nigeria in 1995 and 2020 were estimated. Fifty‐three studies (n = 78 949) met our selection criteria. Estimated crude prevalence of pre‐hypertension (120‐139/80‐89 mmHg) in Nigeria was 30.9% (95% confidence interval [CI]: 22.0%‐39.7%), and the crude prevalence of hypertension (≥140/90 mmHg) was 30.6% (95% CI: 27.3%‐34.0%). When adjusted for age, study period, and sample, absolute cases of hypertension increased by 540% among individuals aged ≥20 years from approximately 4.3 million individuals in 1995 (age‐adjusted prevalence 8.6%, 95% CI: 6.5‐10.7) to 27.5 million individuals with hypertension in 2020 (age‐adjusted prevalence 32.5%, 95% CI: 29.8‐35.3). The age‐adjusted prevalence was only significantly higher among men in 1995, with the gap between both sexes considerably narrowed in 2020. Only 29.0% of cases (95% CI: 19.7‐38.3) were aware of their hypertension, 12.0% (95% CI: 2.7‐21.2) were on treatment, and 2.8% (95% CI: 0.1‐5.7) had at‐goal blood pressure in 2020. Our study suggests that hypertension prevalence has substantially increased in Nigeria over the last two decades. Although more persons are aware of their hypertension status, clinical treatment and control rates, however, remain low. These estimates are relevant for clinical care, population, and policy response in Nigeria and across Africa. Abstract : From 53 studies covering a population of 78 949 Nigerians, we estimated an age‐adjusted prevalence of hypertension of 8.6% in 1995 representing 4.3 million persons aged ≥20 years. Age‐adjusted prevalence increased to 32.5% (27.5 million individuals) in 2020. Of these, 29.0% of (95% CI: 19.7‐38.3) were aware of their hypertension, 12.0% (95% CI: 2.7‐21.2) were on treatment, and 2.8% (95% CI: 0.1‐5.7) had at‐goal blood pressure. Being the most populous country in Africa, our findings offer insights on the current status of hypertension in Africa, and are highly relevant for international comparisons. Improving hypertension awareness and clinical management is a public health priority.